O-GlcNAc modification regulates autophagy and apoptosis in endometriosis - Xiaohan Jin; Yali Feng; Lei Xu; Jing Li; Linping Fan; Jinge Li; Runyuan Liu; Qing Yang; Ying Kong; Yuhong Shang (Functional & Integrative Genomics, 2026)

Electrochemical degradation of dibutyl phthalate in simulated printing and dyeing textile wastewater using cerium and stearic acid-modified Ti/TiO2-NTs/PbO2-Ce-SA electrode - Dexiang Liao; Fan Yang; Linping Tang; Fan Wu; Fang Yin; Lisu Chen; Daolun Feng (Journal of Water Process Engineering, 2026)

A chlorine-rich argyrodite electrolyte with cost-effectiveness and high ionic conductivity for all-solid-state lithium batteries - Shijie Yu; Lin Zheng; Manzhen Fang; Linping Liao; Ting Yang; Peidian Chong; Yafeng Li; Longyuan Guo; Mingdeng Wei (Chemical Engineering Journal, 2026)

Identification of rice paddy field morphology following the collapse of Neolithic culture in the Taihu Lake Plain, the Lower Yangtze River - Haiming Li; Xuan Yi; Huiru Lian; Xuyang Zhang; Duo Zheng; Xuanyi Zhang; Linping Ren; Liu Yang; Zhiping Zhang; Rongfang Song; Zhikun Ma; Harry F. Lee; et al. (Journal of Geographical Sciences, 2026)

Enhancing surface electron donation of single-atom copper catalyst for promoting CO2 electroreduction to CH4 - Bowen Wu; Lu Song; Hairui Ma; Kewei Zhang; Mingtai Liu; Anxiang Guan; Zhengzheng Liu; Chao Yang; Naixin Lyu; Gengfeng Zheng; Linping Qian (Chemical Engineering Journal, 2025)

Comprehensive analysis of intracellular electron transfer and microbial succession in response to florfenicol in mixotrophic denitrification systems - Shaofei Yang; Yunzhu Ding; Linping Tang; Chunji Jin; Yangguo Zhao; Liang Guo (Environmental Research, 2025)

Transplacental transfer of p-phenylenediamine antioxidants: Insights from human gestational exposure and an optimized BeWo cell monolayer model - Junxu Li; Fangfang Ren; Linping Cao; Hangbiao Jin; Yang Li (Journal of Hazardous Materials, 2025)

Occupational aluminum exposure in northern China’s large-scale plants: Unveiling dual-pathway mediation of fasting blood glucose and systolic blood pressure in cognitive impairment among workers - Xin Guo; Qiang Yang; Fangyu Gao; Baolong Pan; Feng Gao; Jingsi Zhang; Shanshan Wang; Xiaoting Lu; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu (NeuroToxicology, 2025)

POD-like nanozyme constructed from perspective of charge transfer engineering for biosensing of magnetic separation treated Listeria monocytogenes - Weiqiang Li; Xiaoyun Xu; Yang Song; Linping Fan; Jin Huang; Luyu Yang; Yang Liu; Hengyi Xu (Food Chemistry, 2025)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

Short-term response of soil fungal community composition and trophic mode to winter mulch management in Lei bamboo (Phyllostachys praecox) forests - Linping Zhang; Nancai Pei; Fei Wu; Na Wu; Zuyao Li; Yuxuan Huang; Mingxi Tan; Ying Yang (Applied Soil Ecology, 2024)

Analysis of aged microplastics: a review - Yanqi Shi; Linping Shi; Hexinyue Huang; Kefu Ye; Luming Yang; Zeena Wang; Yifan Sun; Dunzhu Li; Yunhong Shi; Liwen Xiao; Shixiang Gao (Environmental Chemistry Letters, 2024)
Microplastics are emerging contaminants that undergo progressive aging under environmental conditions such as sunlight irradiation, mechanical forces, temperature variations, and the presence of biological organisms. Since aging modifies microplastic properties, such as their own toxicity and the toxicity of trapped pollutants, advanced methods to analyze microplastics are required. Here we review methods to analyze microplastic aging with focus on the aging process, qualitative identification, quantitative characterization, and chemometrics. Qualitative identification is done by mechanical techniques, thermal techniques, e.g., thermal degradation and gas chromatography–mass spectrometry, and spectral techniques, e.g., infrared, Raman, fluorescent, and laser techniques. Quantitative characterization is done by microscopy and mass spectrometry. Microplastic aging results in a series of surface physical changes, biofilm formation, chemical oxidation, thermal alternation, and mechanical deterioration. Changes in mechanical and thermal properties allow to differentiate aged microplastics. Infrared and Raman spectroscopy are rapid and sensitive for chemical identification of microplastics in complex environmental samples. Combining two techniques is preferable for accurate detection and categorization.

Hybrid chiral nanocellulose-cyanidin composite with pH and humidity response for visual inspection and real-time tracking of shrimp quality and freshness - Yingxuan Feng; Jian Lin; Xinjie Chen; Hao Chai; Linping Tian; Jiayi Zhang; Qingfeng Sun; Yushan Yang; Yingying Li (Food Chemistry, 2024)

Formation of Sb2O3 microcrystals by Rhodotorula mucilaginosa - Linping Yang; Aijiang Yang; Liyan Song; Wen Cui; Wanping Bian; Aping Niu; Peng Xu; Shouyang He; Shixue Mei; Xianrong Shi (Journal of Hazardous Materials, 2024)

The highly effective cadmium-resistant mechanism of Pseudomonas aeruginosa and the function of pyoverdine induced by cadmium - Shixue Mei; Wanping Bian; Aijiang Yang; Peng Xu; Xiaoli Qian; Linping Yang; Xianrong Shi; Aping Niu (Journal of Hazardous Materials, 2024)

Rapid quantitative evaluation of total polar materials (TPM) in frying oil based on an “off-on” fluorescence viscosity response probe - Jiayi Shi; Jian Tao; Yanfeng Fu; Linping Zhao; Ran Yang; Lingbo Qu; Zhaohui Li; Yuanqiang Sun (Analytica Chimica Acta, 2024)

A simulation-optimization approach based on the compound eutrophication index to identify multi-nutrient allocated load - Yanqun Yang; Keqiang Li; Shengkang Liang; Guohong Lin; Cheng Liu; Jixin Li; Linping Xie; Yanbin Li; Xiulin Wang (Science of The Total Environment, 2024)

Reimagining medical sustainability: The role of symbolic visuals against plastic waste - Xiaoping Yang; Ali Hasan; Chia-Hui Yu; Linping Xu; Jiabin Yi (Journal of Cleaner Production, 2024)

The responding mechanism of indigenous bacteria in municipal wastewater inoculated with different concentrations of exogenous microalgae - Xinyue Yang; Linping Liu; Xudong Liu; Shulian Xie; Jia Feng; Junping Lv (Journal of Environmental Management, 2023)

Light-responsive benzobisthiazole as oxidase mimic for rapid determination of glutathione in food and vegetable - Jiao Wu; Lingbo Qu; Zhaohui Li; Linping Zhao; Yuanqiang Sun; Ran Yang (Food Chemistry, 2023)

Effect of actual working conditions on catalyst structure and activity for oxidation of volatile organic compounds: A review - Qiuyu Shen; Zhihui Lu; Fukun Bi; Yuyin Fang; Linping Song; Yang Yang; Minghong Wu; Xiaodong Zhang (Fuel, 2023)

Rapid self-calibrating fluorescent detection of copper (II) ions in wine with high accuracy - Xiuxiu Dai; Zengqiang Liang; Yang Li; Jian Tao; Lingbo Qu; Linping Zhao; Ran Yang (Food Chemistry, 2023)

Identification of a novel frameshift mutation in the SCNN1B causing Liddle syndrome - Yi Qu; Yiting Lu; Di Zhang; Xinchang Liu; Peng Fan; Jiexin Chen; Hanbo Zhang; Kunqi Yang; Tao Tian; Yi Zhou; Qiongyu Zhang; Yu Zhang; et al. (Science Bulletin, 2023)

Factors associated with dysglycemia and its post-surgical resolution in patients with pheochromocytomas - Lin Zhao; Xu Meng; Qiongyu Zhang; Yi Zhou; Ting Zhang; Tao Tian; Hua Fan; Huadong Zhu; Yecheng Liu; Fang Luo; Linping Wang; Weixian Yang; et al. (Science China Life Sciences, 2023)

Mitochondrial sequence polymorphism in Chinese populations of Hylobitelus xiaoi (Coleoptera: Curculionidae) - Haiyan Zhang; Shengli Zhang; Yang Zhang; Linping Zhang; Dong Li; Longxi He; Fenggang Luan (Applied Entomology and Zoology, 2017)